Математическое моделирование и численный анализ течений вязкой несжимаемой жидкости в областях с подвижной границей - Полковниченко, Е. Ю.; Сидоров, М. В.; Шульгина, С. С. (Запоріжжя, ЗНУ, 2014)
Рассматривается задача математического моделирования и численного анализа течений вязкой несжимаемой жидкости в области, граница которой изменяется с течением времени. Математической моделью служит начально-краевая задача для функции тока в двусвязной области. Для её решения предлагается использовать принцип суперпозиции и структурный метод R-функций с аппроксимацией неопределенной компоненты структуры методом Галёркина. Вычислительный эксперимент проведен для случая единичного квадрата с расположенным в нем вращающимся с постоянной угловой скоростью пропеллером. Построены поля скоростей течения в различные моменты времени. This paper considers the problem of mathematical modeling and numerical analysis of viscous incompressible fluid in a region, whose boundary changes over time. The mathematical model is the initial boundary value problem for the stream function in a doubly connected domain. The feature of the problem is in the fact that the boundary conditions contain an unknown beforehand function of a time - the value of the stream function at the inner boundary. To determine this function is proposed to use the integral relation, which provides the uniqueness of the pressure in the doubly connected domain. This condition consists in zeroing taken along the inner boundary curvilinear integral of the normal derivative of the velocity vorticity. To solve this problem, the principle of superposition and structural R-functions method with approximation of uncertain structural components by the Galerkin method is proposed to use.
Keywords: нестационарное течение вязкой жидкости; область с подвижной границей; функция тока; метод R-функций; метод Галёркина; nonstationary viscous fluid flow; domain with movable boundary; stream function; Galerkin’s method; the R-function method